Effect of Diabetes Mellitus and Hypertension on Osmotic Fragility and Hemorheological Factors in Male Wistar Rats - David Ehikhuemen Okonofua; Jerome Ndudi Asiwe; Kenneth Kelechi Anachuna; Emuesiri Goodies Moke; Kamaldeen Olalekan Sanusi; Ebunoluwa Oluwabusola Adagbada; Mariam Onono Yusuf; Damilola Ifeoluwa Alawode; Adesoji Adedipe Fasanmade (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2021)
Diabetes mellitus is a common risk factor for erythrocyte osmotic stress. This study was aimed at exploring the effect of streptozotocin (STZ)-induced diabetes mellitus and salt-induced hypertension on osmotic fragility and hemorheological variables in male Wistar rats. Thirty male rats were grouped into five groups of six animals each as follows: negative control (zero salt in diet); positive control (normal salt diet - 0.3% salt); high salt diet (8% salt) (HSD only); STZ induced diabetes and normal salt diet (STZ only); STZ induced diabetes and high salt diet (STZ + HSD). At the end of a 4 weeks period, hematological variables, osmotic fragility, rheology and cardiovascular responses were assessed. There was an increase (p<0.05) in the mean arterial pressure and heart rate of HSD, STZ and HSD + STZ groups indicating a salt induced hypertension. There was a decrease in the body weight of STZ and HSD +STZ groups. There was significant increase (p<0.05) in the haematocrit, platelets estimates and fibrinogen concentrations in the experimental groups when compared with the controls. The STZ and STZ + HSD groups showed a reduced clotting time which corresponded to the increased platelet estimates and fibrinogen concentration. The increase in haematocrit, platelet and plasma protein resulted in the increased blood viscosity and a decreased flow rate. The osmotic fragility test was also observed to be increased (p<0.05) in HSD, STZ only and STZ + HSD groups. Diabetes mellitus and hypertension increase the rate of hemolysis of erythrocyte, as well as increase blood viscosity.